(untitled) (Revista Española de Fisiología, 1992)
In order to observe the effects of sheep red blood cells (SRBC) administration on the muscle cell growth in malnourished states, adult male Wistar rats (135 +/- 10 g 10 animals per group) subjected during 30 days to 1% and 10% protein diets, were injected (i.v.) either 15.5 x 10(8) sheep red blood cells or 0.5 ml saline/100 g b.w. after 20 days of experiment. On the 10th day after injection the animals were sacrificed and the gastrocnemius muscle was removed, weighed and homogenized. The supernatant fluids were used to evaluate muscle protein, DNA and RNA rates and acid DNase activity. All parameters were depleted in malnourished rats, indicating a muscle cellular atrophy as well as a decrease in muscle protein synthesis per DNA-unit. Muscle hyperplasia and hypertrophy were found in antigenically stimulated rats fed 10% protein against non-stimulated control. In contrast, muscle growth in protein-deficient rats SRBC-treated was unmodified when compared to non-stimulated malnourished muscle, although RNA functionality seems to be enhanced (RNA/DNA). These data suggest that a redistribution of essential nutrients occurred for muscle growth adaptation rather than for defensive mechanism.